QUALITY CULTURE OPTIMIZATION STRATEGY IN IMPROVING THE QUALITY OF HOSPITAL SERVICES - Laila Irawati; Sidik Priadana; Tete Saepudin (Yayasan Putra Adi Dharma, 2026)
Quality culture is an important foundation in improving the quality of health services in hospitals. This study aims to analyze strategies for strengthening quality culture in an effort to improve the quality of services in hospitals in South Tangerang. The study used a qualitative approach with a case study design at XX Hospital and YY Hospital. Data collection was carried out through in-depth interviews, observations, and documentation of hospital leaders, health workers, and service support staff. Data analysis was carried out thematically through data reduction, data presentation, and drawing conclusions. The results of the study indicate that the quality culture in both hospitals has not been optimally formed. This is indicated by the inconsistent implementation of service standards, weak internalization of quality values, delays in services, low compliance with patient safety standards, and limited continuous monitoring and evaluation systems. The strategies for strengthening the quality culture implemented include increasing leadership commitment, strengthening human resource competencies through continuous training, strengthening internal communication, developing an integrated quality assurance system, implementing rewards and punishments, and optimizing the use of hospital information technology. This study concludes that systematic and sustainable strengthening of a quality culture plays a crucial role in improving the quality of hospital services. Management support, involvement of all organizational elements, and consistent implementation of quality standards are key factors in successfully strengthening a quality culture in hospitals.